Kebenaran Pandangan Filsafat : Kajian Ontologi, Epistimologi, dan Aksiologi dalam Pendidikan Islam - Sufiani, Sufiani; Musthan, Zulkifli; Muh. Shaleh (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
Philosophical studies in the fields of ontology, epistemology, and axiology play a crucial role in providing a comprehensive rationale for the development of Islamic Religious Education. Ontology addresses the nature of existence and reality, which in the context of Islamic Religious Education affirms that the existence of humans and the universe originates from God as the Creator. Epistemology highlights the nature of knowledge, its sources, and the means of acquiring it, where Islamic Religious Education views revelation, reason, and experience as primary, complementary sources of truth. Meanwhile, axiology emphasizes the value and purpose of knowledge, which in Islamic Religious Education is directed toward shaping individuals who are faithful, knowledgeable, and virtuous. Through an integrative approach, philosophy provides a conceptual foundation for teachers and students in understanding and internalizing Islamic values ​​critically, rationally, and applicably. Thus, this study demonstrates that the truth of philosophical perspectives is not only relevant in the theoretical realm but also serves as a practical foundation in Islamic Religious Education, aimed at realizing a perfect human being with a balance between spiritual, intellectual, and moral dimensions.